Sex differences in physiology - Neigh, Gretchen; Mitzelfelt, Megan (Academic Press is an imprint of Elsevier, 2016)
This book reviews the published research and methodologies concerning sex differences in normal physiology and disease and examines basic science research into sex differences in all physiological fields, including cardiovascular, respiratory, renal, gastrointestinal, and musculoskeletal physiology.